Pengaruh Label Halal, Citra Merek dan Kualitas Produk Terhadap Loyalitas Pelanggan Mie-Sedap pada Konsumen Toko Basmalah Cabang Muncar - Samsuri Samsuri (RIBHUNA : Jurnal Keuangan dan Perbankan Syariah, 2023)
This study aims to determine whether there is an influence of the halal label variable, brand image and product quality on customer loyalty of the Sedaap brand instant noodles on consumers of Basmalah Stores, Muncar Branch. This study used a quantitative approach with data collection techniques through questionnaires with a Likert scale. This study used 60 consumers of Muncar Branch Basmalah Shop consumers with a purposive sampling technique. Regression analysis results can be seen that the halal label variable, brand image and product quality simultaneously affect customer loyalty 80.6%, and the remaining 19.4% (100% - 80.6%) is influenced by other variables outside the model. Thus it can be concluded that there is an influence of the halal label, brand image and product quality on customer loyalty of the Sedaap brand instant noodles on consumers of Muncar Branch Basmalah Stores.